The timing of the Castelnovisation of southwestern Europe: A Bayesian modelling insight from the Romagnano Loc III rock shelter sequence (Trento, Italy) - Salvador Pardo-Gordó; Alex Fontana; Vanessa Extrem-Membrado; Emilio Vacas-Fumero; Rossella Duches; Elisabetta Flor; Federica Fontana (PLoS ONE, 2025)
This paper provides a review of the Mesolithic sequence at the Romagnano loc III site through Bayesian modelling, combining the radiocarbon dates obtained in the 1970s with more recent 14C dates. The results suggest a chronology associated with the Castelnovian complex that predates those identified in other areas of Southwestern Europe, thus offering a new working hypothesis regarding the origin of this complex. Finally, these findings are discussed within the broader context of the origin and expansion of the Blade Trapeze Complex in Southwestern Europe indicating that the emergence of this new complex was a multifaceted process that can only be fully understood through a comprehensive global approach.